Blue carbon market in Viet Nam: Potential and challenges for future development - Vũ, T.P.; Pham, T.T.; Trần, N.M.H.; Nguyễn, T.T.A.; Nguyễn, T.V.A.; Tăng Thị, K.H. (CIFOR-ICRAF, 2023)
This report was prepared to provide information for policymakers in Vietnam on the potential, opportunities and challenges in designing and implementing policies and project programs. Blue carbon projects include mangroves, peatlands, wetlands, seagrass, and tidal marshes. The report was developed based on policy analysis and secondary documents, online surveys with stakeholders, and consultations with relevant stakeholders through a scientific national consultation workshop.